Aplicativo digital, como herramienta para la identificación de instrumental de odontopediatría, dirigido a los estudiantes de odontología de la Universidad Antonio Nariño (2022)
In the clinic of the Antonio Nariño university, shortcomings in the identification of instruments are observed, which makes it necessary to design a digital application, which allows students to have a tool that makes it easier for them to accurately recognize pediatric dentistry instruments, thus guaranteeing its correct use.